2003
DOI: 10.3201/eid0909.020591
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes and Use of Antibiotics

Abstract: Recent antibiotic use is a risk factor for infection or colonization with resistant bacterial pathogens. Demand for antibiotics can be affected by consumers’ knowledge, attitudes, and practices. In 1998–1999, the Foodborne Diseases Active Surveillance Network (FoodNet) conducted a population-based, random-digit dialing telephone survey, including questions regarding respondents’ knowledge, attitudes, and practices of antibiotic use. Twelve percent had recently taken antibiotics; 27% believed that taking antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(117 citation statements)
references
References 33 publications
(18 reference statements)
9
101
4
1
Order By: Relevance
“…Groups with inadequate knowledge regarding antibiotic use included the elderly (aged ≥ 60), and those of lower socioeconomic or educational status. As we found, a higher educational level has been associated with better knowledge and attitude (Parimi, Pereira, & Prabhakar, 2004;Van den Eng et al, 2003;You et al, 2008), and the elderly are less knowledgeable about antibiotics in general (McNulty et al, 2007a). A unique finding in our study was that respondents aged ≥ 60 had better attitudes than those aged 40-59, even though their knowledge of antibiotics was the lowest overall.…”
Section: Discussionmentioning
confidence: 38%
“…Groups with inadequate knowledge regarding antibiotic use included the elderly (aged ≥ 60), and those of lower socioeconomic or educational status. As we found, a higher educational level has been associated with better knowledge and attitude (Parimi, Pereira, & Prabhakar, 2004;Van den Eng et al, 2003;You et al, 2008), and the elderly are less knowledgeable about antibiotics in general (McNulty et al, 2007a). A unique finding in our study was that respondents aged ≥ 60 had better attitudes than those aged 40-59, even though their knowledge of antibiotics was the lowest overall.…”
Section: Discussionmentioning
confidence: 38%
“…Also that of individuals with a formal education or basic education without a degree will be different from that of completely illiterate consumers of antibiotics. 10 the aim of this study was therefore to examine the knowledge and practice of antibiotic use among students in a university in south western Nigeria so as to know the kind of education on antibiotics that would be applicable to them.…”
Section: Introductionmentioning
confidence: 99%
“…Neste estudo os autores concluíram que a demanda por antibióticos pode ser afectada pelo conhecimento dos consumidores, atitudes e práticas. [19] Em outro estudo realizado em Portugal, no concelho de Vizela, verificou-se que 22,3 % dos inquiridos não sabem o que é um antibióti-co, 13,1 % afirmaram que um antibiótico é usado em infecções virais e apenas 7,9 % afirmaram que um antibiótico é usado no tratamento de infecções bacterianas. O mesmo estudo também verificou que a frequência da toma de antibióticos está relacionada com as variáveis conhecimento e uso de antibióticos e género.…”
Section: 7 953unclassified
“…In this study, authors concluded that the demand for antibiotics might be affected by consumers' knowledge, attitudes and practices. [19] Another Portuguese study, in the municipality of Vizela, found that 22,3 % of respondents did not know what an antibiotic is. 13,1 % said that an antibiotic is used in viral infections and just 7,9 % said an antibiotic is used in the treatment of bacterial infections.…”
Section: Conclusõesmentioning
confidence: 99%